English Language Educational Program Students' Motivation in Learning English Grammar after Covid-19 Pandemic - Rahmadani, Ayuda; Kher, Dinovia Fannil (Journal of English Language Teaching, 2024)
This study aims to know the English Language Educational Program Students’ motivation in learning English Grammar after Covid-19 pandemic viewed from their intrinsic and extrinsic motivation. The sample in this study were 37 students enrolled in the English Educational Program at Universitas Negeri Padang 2021. Researcher used a quantitative research. Data was collected through a questionnaire and interview. Based on this study, the students’ intrinsic motivation was high (73,51%) and the students’ extrinsic motivation was also high (71,31%). The result of the study showed that both of intrinsic and extrinsic motivation was high. This was due to several reasons, namely the students have desire in learning advanced grammar after pandemic to improve their skills, the changing from online learning to offline learning made them feel challenged to learn advanced grammar, student motivation can come from the teaching materials provided by lecturers who teach advanced grammar in class, student said that a punishment from the lecturer can influence them to active at class, and the students’ motivation in learning advanced grammar after pandemic also influenced by the lecturer’ attendance at the class.